Acute effect of myofascial reorganization of the trapezius muscle in peripheral muscle oxygenation in asympomatic subjects – a case series - Sinhorim, Larissa; Amorim, Mayane; Torres, Laureani Jaques; Wagner, Janaína; Niza, Nathália Tiepo; Lemos, Francisco De Paula; Sonza, Verônica Vargas Horewicz Anelise; Santos, Gilmar Moraes (Manual Therapy, Posturology & Rehabilitation Journal, 2019)
Background: Myofascial Reorganization (MFR) is a physiotherapy technique that mixes myofascial pressures and slips and has been used as a simple and non-invasive method that readjusts soft tissues, as well as myofascial adhesions and contractures that may cause decreased blood supply and consequently of physical activity. Objective: To verify if the MFR alters the tissue oxygenation of the trapezius muscle (TM) in subjects without the pain symptom in the evaluation day. Methods: The sample consisted of eight subjects with a mean age of 23 (± 6) years and a body mass index of 23.2 (±15.0) kg.m-2. Changes in muscle oxygenation were measured by near infrared spectroscopy (NIRS) (Portamon, Artinis, the Netherlands) in TM before and after 15 minutes of intervention. The proposed MFR protocol lasted approximately 10 minutes and consisted of pressures, stretching and myofascial slippage of the upper, middle and lower TM fibers. Data normality was performed using the Shapiro Wilk test and due to the parametric nature of the data, the paired t-test was used for pre and post intervention comparison. Results: There was a significant increase in the tissue saturation index (TSI) in the trapezius muscle (80.7±2.7% vs. 89.4±4.6%; p= 0.002) in the pre and post intervention comparison. The pre-post variation delta of oxyhemoglobin - O2 Hb (8.1±11.2 g/dL), deoxyhemoglobin - HHb (-0.72±1.6 g/dL) and total hemoglobin - tHB (7.4±12.3 g/dL) showed no significant difference. However, there was an increase in O2 Hb, tHB levels and a decrease in HHb. Conclusion: The findings showed that the MFR applied on trapezius muscle increased the TSI, which reflects on peripheral muscle oxygenation in subjects without pain in the day of evaluation.